Abundance, classification and genetic potential of Thaumarchaeota in metagenomes of European agricultural soils: a meta-analysis - Johanna Nelkner; Liren Huang; Timo W. Lin; Alexander Schulz; Benedikt Osterholz; Christian Henke; Jochen Blom; Alfred Pühler; Alexander Sczyrba; Andreas Schlüter (Environmental Microbiome, 2023)
Abstract Background For a sustainable production of food, research on agricultural soil microbial communities is inevitable. Due to its immense complexity, soil is still some kind of black box. Soil study designs for identifying microbiome members of relevance have various scopes and focus on particular environmental factors. To identify common features of soil microbiomes, data from multiple studies should be compiled and processed. Taxonomic compositions and functional capabilities of microbial communities associated with soils and plants have been identified and characterized in the past few decades. From a fertile Loess–Chernozem-type soil located in Germany, metagenomically assembled genomes (MAGs) classified as members of the phylum Thaumarchaeota/Thermoproteota were obtained. These possibly represent keystone agricultural soil community members encoding functions of relevance for soil fertility and plant health. Their importance for the analyzed microbiomes is corroborated by the fact that they were predicted to contribute to the cycling of nitrogen, feature the genetic potential to fix carbon dioxide and possess genes with predicted functions in plant-growth-promotion (PGP). To expand the knowledge on soil community members belonging to the phylum Thaumarchaeota, we conducted a meta-analysis integrating primary studies on European agricultural soil microbiomes. Results Taxonomic classification of the selected soil metagenomes revealed the shared agricultural soil core microbiome of European soils from 19 locations. Metadata reporting was heterogeneous between the different studies. According to the available metadata, we separated the data into 68 treatments. The phylum Thaumarchaeota is part of the core microbiome and represents a major constituent of the archaeal subcommunities in all European agricultural soils. At a higher taxonomic resolution, 2074 genera constituted the core microbiome. We observed that viral genera strongly contribute to variation in taxonomic profiles. By binning of metagenomically assembled contigs, Thaumarchaeota MAGs could be recovered from several European soil metagenomes. Notably, many of them were classified as members of the family Nitrososphaeraceae, highlighting the importance of this family for agricultural soils. The specific Loess-Chernozem Thaumarchaeota MAGs were most abundant in their original soil, but also seem to be of importance in other agricultural soil microbial communities. Metabolic reconstruction of Switzerland_1_MAG_2 revealed its genetic potential i.a. regarding carbon dioxide (CO $$_2$$ 2 ) fixation, ammonia oxidation, exopolysaccharide production and a beneficial effect on plant growth. Similar genetic features were also present in other reconstructed MAGs. Three Nitrososphaeraceae MAGs are all most likely members of a so far unknown genus. Conclusions On a broad view, European agricultural soil microbiomes are similarly structured. Differences in community structure were observable, although analysis was complicated by heterogeneity in metadata recording. Our study highlights the need for standardized metadata reporting and the benefits of networking open data. Future soil sequencing studies should also consider high sequencing depths in order to enable reconstruction of genome bins. Intriguingly, the family Nitrososphaeraceae commonly seems to be of importance in agricultural microbiomes.